Diagnostic management of patients reporting symptoms after wheat ingestion - Costantino, Andrea; Aversano, Gloria Maria; Lasagni, Giovanni; Smania, Veronica; Doneda, Luisa; Vecchi, Maurizio; Roncoroni, Leda; Pastorello, Elide Anna; Elli, Luca (Frontiers in Nutrition, 2022)
Many patients report symptoms after wheat ingestion experiencing a wide spectrum of clinical manifestations. Three possible diagnoses have been recognized: celiac disease (CD), wheat allergy (WA), and non-celiac (gluten)wheat sensitivity (NCGS/NCWS). CD is a chronic immune-mediated disease of the small bowel caused by exposure to dietary gluten in genetically predisposed individuals, with a prevalence of approximately 1%. It is characterized by mucosal inflammation and atrophy following exposure to gluten and improvement after gluten withdrawal. Food allergies are immunological responses to a food antigen. WA is the expression of an immunologically mediated process that can be immunoglobulin E (IgE) or non-IgE mediated; its many symptoms include urticaria/angioedema, asthma, rhinitis, and anaphylaxis. NCGS/NCWS is characterized by gastrointestinal and/or extra-intestinal symptoms after ingestion of gluten-containing food in subjects not affected by CD or WA. The aim of this review is to help physicians and nutritionists diagnose the cause of symptoms reported after wheat ingestion, thus avoiding patient frustration, inappropriate testing, and incorrect or missed diagnoses. An algorithm for the diagnostic approach in these patients is provided, to help to diagnose CD, WA, NCGS/NCWS or to identify possible functional disorders as the wheat-sensitive irritable bowel syndrome. A personalized approach, regular follow-up, and the help of a skilled healthcare professional are mandatory for patients with symptoms following wheat ingestion is provided. A gluten-free-diet is often recommended for patients with self-reported gluten/wheat-dependent symptoms; for patients with symptoms similar to those of functional diseases while there is evidence that a low-FODMAP diet could be the first option.